2022
DOI: 10.3389/fpubh.2022.959700
|View full text |Cite
|
Sign up to set email alerts
|

The impact of socioeconomic status and sleep quality on the prevalence of multimorbidity in older adults

Abstract: IntroductionMultimorbidity has become a global public health concern that can cause serious damage to the health status of older adults. This study aimed to investigate the impact of socioeconomic status (SES) and sleep quality on the prevalence of multimorbidity in older adults, thus providing a reference for reducing the risk of the prevalence of multimorbidity and improving the health of older adults.MethodsA multi-stage random sampling method was used to conduct a questionnaire survey on 3,250 older adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…These unhealthy habits are recognized as factors associated with chronic diseases (27). Moreover, an increased risk of chronic diseases was associated with more medical visits.…”
Section: Discussionmentioning
confidence: 99%
“…These unhealthy habits are recognized as factors associated with chronic diseases (27). Moreover, an increased risk of chronic diseases was associated with more medical visits.…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors had analysed a unidirectional association between sleep quality and multimorbidity, and a majority of their studies were congruent with our study. For example, a cross-sectional study on 3250 individuals aged 60 years and older in Shanxi Province of China showed that poor sleep quality was associated with the prevalence of multimorbidity (OR = 2.445; 95% CI, 2.043–2.927) [ 21 ], and a recent longitudinal study also indicated that poor sleep quality correlated with an increased risk of multimorbidity (RR: 1.750; 95% CI, 1.476–2.076) [ 18 ]. Regarding sleep duration and multimorbidity, previous studies have shown that short sleep duration increased the risk of cardiovascular diseases [ 22 ], hypertension [ 23 ], and asthma [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the socioeconomic characteristic layer, having a primary education and below was considered to be risk factors for multimorbidity. The association between lower education and multimorbidity is unsurprising, given the well-established evidence that the knowledge and awareness of chronic disease prevention and the control of less educated people may be even lower, increasing the risk of developing multimorbidity [ 62 ]. At the macro-environmental characteristic layer, our study did not find an impact of the policy environment on older people with multimorbidity.…”
Section: Discussionmentioning
confidence: 99%